Rencana pemeliharaan taman Museum Arma Ubud - Sinaga, Stephany; Semarajaya, Cokorda Gede Alit; Mayadewi, Ni Nyoman Ari (Jurnal Arsitektur Lansekap; Vol.5, No.2, Oktober 2019DO - 10.24843/JAL.2019.v05.i02.p07, 2019)
Maintenance plan for the Arma Ubud Museum park. Arma Museum is one of the attractions in Bali that displays art the Balinese culture.The Arma Museum also includes the environment or landscapes in the tourism activities through a park covering an area of 1.5 Ha, so that the Arma museum needs to maintain and preserve the existing park through well-planned park maintenance. The purpose of this research is to plan an ideal garden maintenance program for the Arma museum park. The research method based on its purpose is research and development research methods. The data needed in the study include several aspects related to the formation of the Arma musuem park, namely; biotic and abiotic aspects, social aspects, economic aspects, as well as aspects of the physical maintenance of the park, and aspects of organizing the maintenance of the park. Data analysis used in this study is an analysis of the application of theory and SWOT analysis. Based on the biotic and abiotic aspects, the social aspects, the economic aspects that have been identified indicate the Arma museum park has a lot of potential that needs to be maximized, maintained, and preserved, but the aspect of physical maintenance of the park and the organizing aspects of the maintenance of Arma Musuem park are still not maximized, the results of the application analysis The theory found a gap between ideal action and actual action in the field, through the identified gaps, the plan for organizing effective park maintenance was organized by reducing existing gaps, while the SWOT Analysis produced seven recommendations for strategic plan.